Study On Pozzolanic Reaction And Fluidity Of Blended Cement Containing Treated Palm Oil Fuel Ash As Mineral Admixture - Chea , Chandara (2011)
The aim of this work is to study on pozzolanic reaction and fluidity of blended cement containing treated palm oil fuel ash as mineral admixture. Palm oil fuel ash (POFA) was ground in a ball mill to produce ground palm oil fuel ash (GPOFA), and further treated at 500 °C for 1 hour to remove the unburned carbon, namely treated ground palm oil fuel ash (TGPOFA). Raw materials have been characterized in terms of chemical composition, carbon content, mineral composition, morphology and physical properties.